Activity overlap between mesocarnivores and prey in the Central Mongolian steppe. Issue 5 (3rd September 2022) - Augugliaro, Claudio; Anile, Stefano; Munkhtsog, Bariushaa; Janchivlamdan, Choikhand; Batzorig, Enkhzorig; Mazzon, Ivan; Nielsen, Clayton
Abstract : Research on the ecology and behaviour of mesocarnivores and their prey is scant in Mongolia. We investigated activity patterns of a guild of mesocarnivores (red fox, Pallas's cat and beech marten) and their prey (Siberian marmot, Daurian pika, Brandt vole, Mongolian gerbil and Mongolian silver vole) using 21 camera traps (effort = 1155 camera days) in Central Mongolia from 25st of May to 20th August 2019. Activity patterns of mesocarnivores were cathemeral (i.e. no difference between diurnal, nocturnal and crepuscular detections, although activity peaked at sunrise). Among prey, the Siberian marmot and the Daurian pika were diurnal, whereas the Mongolian gerbil and the Mongolian silver vole were not generally crepuscular. Beech marten, the smallest mesocarnivore species, was temporally segregated from the other (and larger) mesocarnivore species. Temporal segregation between mesocarnivores and prey was evident between the following pairs: red fox vs Brandt's vole and Mongolian gerbil; Pallas's cat vs Siberian marmot, Brandt's vole and Mongolian gerbil; and beech marten vs Siberian marmot, Daurian pika and the Mongolian silver vole. Activity overlap between mesocarnivores and prey ranged considerably. Activity overlap between the beech marten and prey was lower than that of the other mesocarnivores. Temporal overlap among mesocarnivores and between mesocarnivores and prey seemed to be related to species-specific traits, while also being mediated by local prey abundance. We suggest future surveys should be stratified based on habitat and on the target species, while also integrating different survey methods (e.g. camera traps and live trapping of small mammals).